A Longitudinal Study on Maternal Depressive Symptoms During the COVID-19 Pandemic: The Role of Strict Lockdown Measures and Social Support - Joana Fernandes; Inês Tavares; Pedro Bem-Haja; Tânia Barros; Mariana L. Carrito (Frontiers Media S.A., 2022)
Objectives: This study examined the trajectory of perinatal depressive symptoms in Portuguese women during the COVID-19 pandemic and the role of individual, relational, and contextual risk and protective factors.Methods: This 3-wave longitudinal study followed 290 pregnant women from the third trimester of pregnancy until 6-months postpartum. Women self-reported on depressive symptoms, psychological (anxiety, perceived stress, mindfulness), relational (perceived social support, dyadic adjustment, sexual wellbeing), and contextual (lockdown status) factors.Results: Women who were under strict lockdown presented significantly higher scores of depressive symptoms at baseline (by 1.38 EPDS points) than women who were not under strict lockdown measures. Mixed Growth Models showed that trajectories of depressive symptoms were explained by differences in women's baseline depression. Differences in women's depressive symptoms at baseline were mainly explained by higher anxiety and lower social support (22% and 24% for women under lockdown; 39% and 6% for women not on lockdown, respectively).Conclusion: Preventative interventions targeted at pregnant women should aim to reduce anxiety and enhance women's social support to prevent depression in pregnancy and postpartum during the COVID-19 pandemic.